Perspektif dan Pemahaman Kaum Muda Pinggiran Kota (Suburban) terhadap Kekerasan berbasis Gender Online - Syarifah, Imro Atu; Khoirunisa, Divanda Aya Sofia; Puspitaningsih, Vera Arista; Hafifah, Helena Nuryatul; Wisanti, Vania Casimira Trani; Andina, Tri Kurnia Revul (Jurnal Studi Pemuda, 2024)
The rapid development of digital technology presents new challenges, particularly in addressing online gender-based violence (OGBV), which also impact young people in suburban areas of Indonesia. This study aims to explore the perspectives and understanding of suburban youth regarding OGBV and its prevention, based on the assumption that there are significant gaps in information and intervention efforts aimed at eliminating such violence. This research adopts a constructive paradigm and employs a phenomenological research method focusing on young people aged 18-35 both women and men, in Tanjungharjo Village, Kulonprogo, and Gari Village, Gunung Kidul, in the Special Region of Yogyakarta, Indonesia. The main objectives are to examine suburban youth’s perspectives on OGBV cases in Indonesia and to gain deeper insights into their understanding of OGBV preventions and handlings. The findings show that young people’s perspectives on OGBV are highly diverse, shaped by factors including social norms, patriarchal culture, lack of education and intervention related to gender equality and OGBV. Furthermore, their awareness and knowledge of procedures for preventing OGBV are relatively low. This research serves as a foundation for formulating intervention and prevention programs for OGBV in Indonesia. Such programs should move beyond urban-centric approaches and instead be tailored to the specific conditions and needs of suburban youth.